Advances in trans studies : moving toward gender expansion and trans hope - Johnson, Austin H.; Rogers, Baker A.; Taylor, Tiffany, 1972- (Emerald Publishing Limited, 2021)
This volume of Advances in Gender Research gives space and voice to trans peoples' experiences and interactions with various social institutions, including but not limited to, social media, healthcare and medicalization, the criminal justice system, and the family. The chapters in this volume utilize intersectional approaches, qualitative and quantitative methodologies, and many have clear implications for policy and advocacy for trans and gender diverse people. The first part of the book covers a wide array of issues relating to health and healthcare for trans people, with authors examining health and aging for older trans people, the continued cisnormativity and transphobia that plagues the healthcare field, questions of body modification and how this relates to fertility, as well as access to mental health care. Part two explores trans inclusion in institutions and societies around the world, with authors exploring non-binary gender options on state sanctioned identification, prison experiences and policy recommendations in the U.S. and England, and positive changes to support trans students on college campuses. Part three covers trans resources, healing, and resilience. The aim of this volume is greater than merely updating the research in trans studies, it stems from a desire to support the trans community in the continued fight for recognition and rights. The volume urges scholars to better understand gender expansion and to turn more attention towards trans hope. To encourage this, the volume ends with a section on resources, healing, and resilience, paving the way for the future of trans studies in sociology.
Includes index.
Keywords: Transgender people.; Gender nonconformity.; Social Science, LGBTQ+ Studies, Transgender Studies.; Gender studies: transsexuals & hermaphroditism.; elektronické knihy; electronic books